Peran Guru PAI Dalam Mengatasi Kesulitan Belajar Dalam Pembelajaran Tahfidzul Qur'an Di MTS Darul Funun El-Abbasiyah Padang Japang Kabupaten 50 Kota - Nurhasnah (Jurnal Sakinah, 2022)
This research is motivated by a phenomenon that the authors found from the initial observations, namely the many difficulties faced by students when learning Tahfidzul Qur'an such as easily forgetting the verses that have been memorized, not yet mastering the Makharijul letters, having mental disorders, and lack of concentration in memorizing Al-Qur'an. - Qur'an, feeling lazy, still confused about dividing the schedule between time to focus on school and time to focus on adding to the memorization of the Qur'an, there is a sense of impatience to add memorization but muroja'ah for verses that have been memorized are still chaotic, and the emergence of a sense of pessimism in the memorizer. This has a bad effect on students' memorization of the Qur'an. This study aims to find out how the role of PAI teachers in overcoming students' difficulties in learning Tahfidzul Qur'an at MTs Darul Funun El-Abbasiyah Padang Japang Kab. 50 Cities. This research is a field research (field research) using a qualitative descriptive method, which describes the events that occur in the field as they are. The data collection technique is through observation and interviews. The supporting informants are teachers and documents. After the data is collected, the writer analyzes the data by examining all available data from various sources and then making data reduction by making abstractions. Based on the results of research that the author did at MTs Darul Funun El-Abbasiyah Padang Japang Kab. 50 Cities are: in overcoming the difficulties that students are currently facing at MTs Darul Funun El-Abbasiyah Padang Japang Kab. 50 Cities are Ustad/ustazah using the wahdah method to facilitate reading, providing muroja'ah and talqin assistance, as well as motivation from Ustad/ustadzah to restore enthusiasm that has begun to decline, and 24 hours assistance.